Development of a Sensitive Bioluminogenic Probe for Imaging Highly Reactive Oxygen Species in Living Rats. (16th October 2015) - Kojima, Ryosuke; Takakura, Hideo; Kamiya, Mako; Kobayashi, Eiji; Komatsu, Toru; Ueno, Tasuku; Terai, Takuya; Hanaoka, Kenjiro; Nagano, Tetsuo; Urano, Yasuteru
Abstract: A sensitive bioluminogenic probe for highly reactive oxygen species (hROS), SO3 H‐APL, was developed based on the concept of dual control of bioluminescence emission by means of bioluminescent enzyme‐induced electron transfer (BioLeT) and modulation of cell‐membrane permeability. This probe enables non‐invasive visualization of physiologically relevant amounts of hROS generated deep inside the body of living rats for the first time. It is expected to serve as a practical analytical tool for investigating a wide range of biological functions of hROS in vivo. The design concept should be applicable to other in vivo bioluminogenic probes. Abstract : Warnleuchte : Eine empfindliche bioluminogene Sonde für hoch reaktive Sauerstoffspezies (hROS) beruht auf einer doppelten Kontrolle der Biolumineszenz durch enzyminduzierten Elektronentransfer und Modulierung der Zellmembrandurchdringung. Die Sonde ermöglicht eine nichtinvasive Visualisierung physiologisch relevanter Mengen an hROS, die tief im Körperinneren lebender Ratten gebildet werden.